Effect of Gender on Access to Loans and Borrowed Amount in Malawi - Elisa Nathan Ebiyamu; George Kaudza-Masina (Business, Management and Economics: Research Progress Vol. 10, 2025)
Access to loans is vital for households to supplement their current flow of income as they strive to meet their consumption and investment expenditure needs. The purpose of this study was to determine the effect of gender on access to loans and the amount of money that is borrowed. Gender disparities in access to loans put one gender at an economic disadvantage that might expose them to exploitation in marriages and society at large. This research used a cross-section national data set called the Fifth Integrated Household Survey (IHS 5) that was collected from 2019 to 2020 by the National Statistical Office (NSO). Data were analyzed quantitatively by using descriptive statistics and econometric models. A probit model was used to assess the effect of gender on access to credit and a multiple regression model was used to determine the effect of gender on the amount of money a household borrowed. The key findings of this study show that being female significantly increases the probability of accessing loans by 0.049 or 5 percent compared to male counterparts. However, it reduces the amount of borrowed money by 22 percent on average compared to male borrowers. Education was found to have a positive effect on both access to credit and the amount of credit. To increase the amount of money that women borrow, the study recommends that public loan programs like the National Economic Empowerment Fund (NEEF) must put in place deliberate mechanisms aimed at increasing the amount of money they lend to women. A policy that makes the government a grantor when women want to borrow large amounts of money was proposed. This would encourage women to increase the amount borrowed and also raise lenders’ trust in female borrowers.